1997
DOI: 10.1073/pnas.94.7.3223
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of insulin secretion by insulin-like growth factor 1 is mediated through activation of phosphodiesterase 3B

Abstract: Both insulin and insulin-like growth factor 1 (IGF-1) are known to reduce glucose-dependent insulin secretion from the ␤ cells of pancreatic islets. In this paper we show that the mechanism by which IGF-1 mediates this effect is in large part through activation of a specific cyclic nucleotide phosphodiesterase, phosphodiesterase 3B (PDE3B). More specifically, in both isolated pancreatic islets and insulin-secreting HIT-T15 cells, IGF-1 inhibits insulin secretion that has been increased by glucose and glucagonl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
115
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(125 citation statements)
references
References 35 publications
9
115
0
1
Order By: Relevance
“…Insulin and IGF-1 increase levels of PDE3B in β cells. Treatment of HIT-T15 cells (a hamster clonal β cell line) with IGF-1 (50 nM) roughly halved the insulin secreted in response to GLP-1 (10 nM) in the presence of high levels (12 mM) of glucose (Zhao et al, 1997). This directly correlated to an equivalent reduction in cAMP levels.…”
Section: Stimulation Of Camp Productionmentioning
confidence: 96%
“…Insulin and IGF-1 increase levels of PDE3B in β cells. Treatment of HIT-T15 cells (a hamster clonal β cell line) with IGF-1 (50 nM) roughly halved the insulin secreted in response to GLP-1 (10 nM) in the presence of high levels (12 mM) of glucose (Zhao et al, 1997). This directly correlated to an equivalent reduction in cAMP levels.…”
Section: Stimulation Of Camp Productionmentioning
confidence: 96%
“…Insulin, IGF-1, or IL-4, each of which utilizes IRS proteins to initiate at least some of its receptor signaling cascades, activates PDE3 in adipocytes (16,17,21), FDCP2 cells, pancreatic ␤ cells (77), hepatocytes (78), and Xenopus oocytes (8,79,80). In these cells, some effects of the polypeptides are counterregulatory to those of cAMP, which increases lipolysis (19,20,81), inhibits cell proliferation/survival (41-55), stimulates insulin secretion (77) and glycogenolysis (82), and blocks meiosis (8), respectively.…”
Section: Effects Of Pde Inhibitors and Camp On Bad Phosphorylation Anmentioning
confidence: 99%
“…Since it has recently been shown that PDE3B is controlled by a variety of hormones in addition to insulin and catecholamines, such as leptin [12,13] Manganiello, unpublished work), IL-4 [11] and growth hormone [15], it is possible that the new phosphopeptides identified in this work contain sites phosphorylated by kinases activated by these signalling molecules. The identities of the kinases involved and the physiological significance of these phosphorylations are presently being investigated.…”
Section: Figure 4 Phosphorylation Of Pde3b In Adipocytes In Response mentioning
confidence: 97%
“…Pierce, T. Rahn Landstro$ m, M. Quon, E. Degerman and V. Manganiello, unpublished work). PDE3B has also been shown to be activated in FDCP2 cells in response to interleukin 4 (IL-4) [11], in pancreatic β-cells in response to IGF-I [12], leptin [13] and glucagon-like peptide 1 [13], in autoreactive CD4 + T cell clones specific for myelin basic protein in response to antigen stimulation [14] and has also been shown to be involved in Abbreviations used : PP, protein phosphatase ; PP1c, PP2Ac, catalytic subunits of PP1 and PP2A respectively ; IGF-I, insulin-like growth factor I ; PDE, phosphodiesterase ; C 13 E 12 , a non-ionic alkyl poly(oxyethylene glycol) detergent ; IL-4, interleukin 4. 1 To whom correspondence should be addressed (e-mail svante.resjo!medkem.lu.se).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation